Climate change mitigation options among farmers in South Asia - Aryal, Jeetendra Prakash; Rahut, Dil Bahadur; Sapkota, Tek Bahadur; Khurana, Ritika; Khatri-Chhetri, Arun (Springer, 2020)
Agriculture in South Asia is highly vulnerable to climate change due to increasing variability in rainfall and rising temperatures leading to the incidence of extreme climatic events such as floods, droughts, heat/cold waves, and storms. Agriculture sector also contributes to the causes of climate change through the emission of greenhouse gasses (GHGs). Hence, adaptation-led mitigation measures are required to sustain agricultural productivity, farm income and reduce GHG emissions wherever possible. This study presents a systematic review of agriculture emission reduction opportunities with a particular focus on agricultural production systems in South Asia. Our review indicates that the adoption of better soil, water, nutrient management practices, and technologies has enormous potential to reduce GHG emissions from agriculture, thereby contributing to the mitigation of climate change. Many existing practices and technologies have the potential to improve both adaptation and mitigation in agriculture which can significantly contribute to complying with nationally determined contributions (NDCs) of South Asian countries. However, barriers to the adoption of GHG mitigating agricultural practices, mainly the financial and institutional barriers, need to be appropriately addressed to achieve the desired level of mitigation.